2016
DOI: 10.1038/srep29251
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the matched-sample bottleneck: an orthogonal approach to integrate omic data

Abstract: MicroRNAs (miRNAs) are small non-coding RNA molecules whose primary function is to regulate the expression of gene products via hybridization to mRNA transcripts, resulting in suppression of translation or mRNA degradation. Although miRNAs have been implicated in complex diseases, including cancer, their impact on distinct biological pathways and phenotypes is largely unknown. Current integration approaches require sample-matched miRNA/mRNA datasets, resulting in limited applicability in practice. Since these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 63 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…The purified mRNA samples were subjected to gene microarray studies by utilizing Clariom S Human gene array (Affymterix, Santa Clara, CA, USA) per manufacturing instructions. The results of the microarray studies were validated and analyzed for variation in pathways of through iPathway guide analysis (Advaita Corporation, Plymouth, MI, USA) 66 . This method scores the pathway by the level of protein expression in cells during drug treatments through Impact Analysis method 67,68 .…”
Section: Methodsmentioning
confidence: 99%
“…The purified mRNA samples were subjected to gene microarray studies by utilizing Clariom S Human gene array (Affymterix, Santa Clara, CA, USA) per manufacturing instructions. The results of the microarray studies were validated and analyzed for variation in pathways of through iPathway guide analysis (Advaita Corporation, Plymouth, MI, USA) 66 . This method scores the pathway by the level of protein expression in cells during drug treatments through Impact Analysis method 67,68 .…”
Section: Methodsmentioning
confidence: 99%
“…The approaches in the second category combine sample-matched studies from multiple data types and provide biomarkers that can capture data heterogeneity present across the omic layers. Integrating such information from multiple data types is essential for obtaining a comprehensive overview of the given biological system and thought to provide better prognostic markers (Berger et al, 2013 ; Kristensen et al, 2014 ; Nguyen et al, 2016b ). For instance, it has been shown that integrating miRNA and mRNA expression profiles results in greater statistical power and better understanding of the underlying disease phenomena, both in the context of biomarker discovery (Volinia and Croce, 2013 ; Wotschofsky et al, 2016 ) and pathway analysis (Calura et al, 2014 ; Vlachos et al, 2015 ; Alaimo et al, 2016 ; Diaz et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to improve reproducibility is integrating multiple microarray datasets via gene expression meta-analysis, which has proven useful in practice because it produces results that validate in independent datasets (1422). Gene expression meta-analysis is often performed using data from growing public repositories such as the National Center for Biotechnology Information's (NCBI) Gene Expression Omnibus (GEO) and the European Bioinformatics Institute's (EBI) ArrayExpress, which together house over 70 000 datasets composed of over 1.7 million assays.…”
Section: Introductionmentioning
confidence: 99%